Mubtada’ and Khobar in the Arabic Sentence Formation in the Nahwu Basic Theory Book - Ghofur, M Abdul; bin Nafsah, Nor Holis; Abdul Jalil Mannan, Ahmad Mizan Rosyadi; Mubarok, Achmad Hadi (Al-Fusha : Arabic Language Education Journal, 2026)
In everyday life, humans cannot be separated from the use of language as a means of communication. However, not many people realize that even a simple sentence structure, such as "This is a book," contains components that play an important role in its meaning. In the Arabic context, the sentence consists of mubtada’ (subject) and khobar (predicate), two fundamental elements that form the basis of sentence formation. The aim of this research is to identify and analyze the role of mubtada’ and khobar in the formation of Arabic sentences. In this research, the researcher chose a qualitative method using library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. The conclusion of this research shows that mubtada’ and khobar have an important role in forming Arabic sentences. Mubtada’ functions as the subject, while khobar furnishes the information needed to explain the subject. A deep understanding of these two elements is necessary so that students, especially beginners, can build a strong foundation in Arabic grammar and be able to construct meaningful and effective sentences.